The genus Diachasmimorpha Viereck (Hymenoptera: Braconidae: Opiinae) from China - Wu, Qiong; Chen, Xue-Xin; He, Jun-Hua (Zootaxa, 2005)
The species of Diachasmimorpha Viereck from China are revised. A key to species is provided and the following new species are described: D. palleomaculata sp. nov., D. bicolor sp. nov., D. dicrocarinata sp. nov., D. flavifacialis sp. nov., D. melathorax sp. nov., D. curvinervis sp. nov. and D. ammanotus sp. nov. D. longicaudata (Ashmead, 1905) is recorded from China for the first time.